The Relationship Between Health Changes and Community Health Screening Participation Among Older People - Du, Benfeng; Mu, Yuexuan (Frontiers in Public Health, 2022)
The utilization of health screening and other community health services has been a hot topic in China. This study examined the effect of health changes (self-rated health, physical health, and mental health) on the community health screening participation of the elderly in China. The data were derived from the 2016 and 2018 waves of the Chinese Longitudinal Aging Social Survey (CLASS). This paper included 10,992 observations in two waves. A fixed effects model was used to test the causal relationship. Approximately 29.56 percent of the respondents participated in a health screening. Notably, after controlling for covariates, changes in mental and physical health both significantly influenced seniors’ participation in health screenings (self-rated health: odds ratio (OR) = 1.206, 95 percent confidence interval (95% CI)= -0.037-0.413; physical health: OR=1.081, 95% CI=0.032-0.124; mental health: OR=0.917, 95% CI=-0.057, -0.002). Age, educational level, income level, and family support were found to be significant factors associated with community health screening participation. Additionally, we identified a mediating effect of mental health between self-rated health and health screening participation, and the suppressing effect of physical health between self-rated health and health screening participation. The results highlight the important role that health changes play in influencing participation in and promotion of health screening in China. On this basis, healthcare providers in the community may consider health changes as a screening criterion to promote health screening, which could be used to guide other health promotion and prevention programs in the community, whilst also promoting healthy aging.